2019
DOI: 10.1002/arch.21541
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporally different expression of alternatively spliced GABA receptor subunit transcripts in the housefly Musca domestica

Abstract: Insect γ-aminobutyric acid (GABA) receptors are important as major inhibitory neurotransmitter receptors and targets for insecticides. The housefly GABA receptor subunit gene MdRdl is alternatively spliced at exons 3 (a or b) and 6 (c or d) to yield the variants of ac, ad, bc, and bd combinations. In the present study, the expression of the MdRdl transcript in the body parts and in the developmental stages of the housefly Musca domestica was examined by quantitative polymerase chain reaction using specific pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 50 publications
4
9
0
Order By: Relevance
“…GABA receptor is highly expressed in the neuronal tissues such as brain and ganglia (Kita et al . ), which is in accordance with our result that expression levels of GABA receptor were significantly higher in head and thorax than in abdomen.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…GABA receptor is highly expressed in the neuronal tissues such as brain and ganglia (Kita et al . ), which is in accordance with our result that expression levels of GABA receptor were significantly higher in head and thorax than in abdomen.…”
Section: Discussionsupporting
confidence: 93%
“…GABA receptor is highly expressed in the neuronal tissues such as brain and ganglia (Kita et al 2019), which is in accordance with our result that expression levels of GABA receptor were significantly higher in head and thorax than in abdomen. Expression pattern of the 12 genes related to insecticide resistance under insecticide stress condition could certify possible involved in detoxification of exogenous compounds to adapt environment.…”
Section: Discussionsupporting
confidence: 92%
“…41−43 In addition, flunitrazepam, which is a representative benzodiazepine allosteric modulator in mammalian GABA A Rs, is a much less effective modulator in the RDL receptors, whereas flunitrazepam was reported to enhance GABAinduced responses in native insect GABARs. 39,40,44 Alternative splicing of rdl at exons 3 and 6 produces four subunit isoforms: RDL ac , RDL ad , RDL bc , and RDL bd 39,45,46 (Figure 3). GABAR agonists and antagonists have different effects on RDL GABARs containing these four splice variants, 47−49 and thus, alternative splicing may increase the physiological and pharmacological diversities of insect RDL GABARs.…”
Section: Insect Gabarsmentioning
confidence: 99%
“…In comparison to mammalian GABAR subunits, the RDL subunit has a longer M3–M4 intracellular loop and the RDL receptor exhibits different pharmacological properties. For instance, insect RDL GABARs are not sensitive to the GABA A R antagonist bicuculline and are activated by both the GABA A R agonist muscimol and the GABA C R agonist 4-aminocrotonic acid. In addition, flunitrazepam, which is a representative benzodiazepine allosteric modulator in mammalian GABA A Rs, is a much less effective modulator in the RDL receptors, whereas flunitrazepam was reported to enhance GABA-induced responses in native insect GABARs. ,, Alternative splicing of rdl at exons 3 and 6 produces four subunit isoforms: RDL ac , RDL ad , RDL bc , and RDL bd ,, (Figure ). GABAR agonists and antagonists have different effects on RDL GABARs containing these four splice variants, and thus, alternative splicing may increase the physiological and pharmacological diversities of insect RDL GABARs. , RNA editing further diversifies insect GABA receptors. , The RDL receptors expressed in Xenopus oocytes or cell lines should serve as a convenient model to study insect GABARs or as a suitable platform that can be used to screen novel GABAR-targeting insecticides.…”
Section: Insect Gabarsmentioning
confidence: 99%
“…To date, three candidate genes, RDL (resistance to dieldrin), LCCH3 (ligand-gated chloride channel homologue 3), and GRD (GABA and glycine-like receptor of Drosophila ), are considered as iGABA receptor subunits in insects. ,, RDL has been studied in several insect species, such as fruit fly Drosophila melanogaster, small brown planthopper Laodelphax striatellus, and honeybee Apis mellifera. Due to amino acid sequence homology, it has been suggested that the 8916 gene is a putative GABA receptor subunit that has been identified in many insect species including D. melanogaster, L.…”
Section: Introductionmentioning
confidence: 99%